Growth differentiation factor-15 and all-cause mortality in patients with suspected myocardial infarction. (1st October 2019) - ,; Giménez, Maria Rubini; Puelacher, Christian; Kozhuharov, Nikola; Morawiec, Beata; Rentsch, Katharina; Miró, Òscar; Martin-Sanchez, F. Javier; Muzyk, Piotr; Geigy, Nicolas; Keller, Dagmar I.; Reichlin, Tobias; et al.
Abstract: Background: To assess the prognostic performance of Growth differentiation factor-15 (GDF-15) concentrations in unselected patients presenting with suspected acute myocardial infarction (AMI) and adjudication based on high-sensitivity cardiac troponin (hs-cTn). Methods and results: In an ongoing prospective multicenter diagnostic study, consecutive patients presenting with suspected AMI to the emergency department and available GDF-15 and hs-cTnT concentrations were included. Adjudication of AMI was performed central by two independent cardiologists using all available clinical information including cardiac imaging and serial hs-cTn concentrations. Overall, 718 patients were included, with 23% (162/718) having an adjudicated diagnosis of AMI. The cumulative incidence of death within 2 years was 19% in patients with AMI (30 deaths in 162 patients) versus 5% in patients without AMI (25 deaths in 556 patients; P < 0.001). In AMI patients, GDF-15 provided an AUC of 0.89 (95% confidence interval [CI] 0.83–0.94) for 2-year death versus 0.55 (95% CI 0.44–0.66) for hs-cTnT ( P < 0.001). A GDF-15 cutoff of ≤1560 ng/L predicted 2-year survival in 47% (76/162) of AMI patients and had 100% sensitivity (95% CI 88–100%) for 2-year death. In patients without AMI, GDF-15 provided an AUC of 0.83 (95% CI 0.76–0.89) versus 0.76 (95% CI 0.67–0.85) for hs-cTnT ( P = 0.096). A GDF-15 cutoff of ≤886 ng/L predicted 2-year survival in 37% (203/556) of non-AMI patients and had 100% sensitivity (95% CI 86–100%) for 2-year death. Conclusions: GDF-15 concentrations at emergency department presentation have a high predictive accuracy for all-cause death in patients with suspected AMI and allow the identification of a large proportion of AMI patients with very low mortality risk. Highlights: In hs-cTn adjudicated AMI patients GDF-15 predicts survival with very high accuracy. GDF-15 identified more AMI patients with very low death risk than the GRACE score. GDF-15 has independent and high discriminative ability for 2-year death.